Before we are born essentials of embryology and birth defects - Moore, Keith L. (Saunders, 2003)
A text on human embryology featuring hundreds of clinical photos, three-dimensional drawings, micrographs, and ultrasound and MR images, covering the week-by-week physical development of the human embryo and discussing congenital anomalies.